Experimental Modeling Of Microcrack Formation In Rocks - Takao Kobayashi (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1982)
Micro-crack formation zones developed near a crack tip in rocks and ceramics play a significant role in fracture behavior of these materials. In order to study micro- crack formation near a crack tip and its effects on crack behavior, a mica-epoxy composite material was developed. Multi-layer mica flakes were embedded in an epoxy matrix. Under high stress in the vicinity of a crack tip the mica delaminated, simulating the micro-cracking along grain boundaries or crystal planes in rocks and ceramics. A compact tension specimen was fabricated from mica-epoxy composite material. During the test the load and crack opening displacement were measured following the ASTM E561 (R-curve determination) procedure. Through the compliance calibration method the effective crack length and the KR were computed. The experiment clearly demonstrates the formation of micro-cracks and their effects on the overall behavior of the specimen. The paper discusses the significance of micro-crack formation on fracture toughness characterizations, and the advantages of the use of mica-epoxy composite for detailed studies of interaction between the micro-crack formation zone and the specimen geometry and size.